Dimensional accuracy of regular- and fast-setting vinyl polysiloxane impressions using customized metal and plastic trays: an in vitro study - Waldecker, Moritz; Jetter, Karla; Rues, Stefan; Rammelsberg, Peter; Zenthöfer, Andreas (Materials, 2025)
The aim of this study was to compare the dimensional accuracy of vinyl polysiloxane impressions differing in terms of curing time (regular-setting (RS) or fast-setting (FS)) in combination with different tray materials (metal (M) and plastic (P)). A typodont reference model simulated a partially edentulous maxilla. Reference points were given by center points of either precision balls welded to specific teeth or finishing-line centers of prepared teeth. These reference points enabled the detection of dimensional deviations between the digitized reference and the scans of the models achieved from the study impressions. Twenty impressions were made for each of the following four test groups: RS-M, RS-P, FS-M and FS-P. Global scan data accuracy was measured by distance and tooth axis deviations from the reference, while local accuracy was determined based on the trueness and precision of the abutment tooth surfaces. Statistical analysis was conducted using ANOVA accompanied by pairwise Tukey post hoc tests (α = 0.05). Most of the distances tended to be underestimated. Global accuracy was favorable; even for long distances, the mean absolute distance deviations were < 100 µm. Local accuracy was excellent for all test groups, with trueness ≤ 11 µm and precision ≤ 9 µm. Within the limitations of this study, all impression and tray materials were suitable to fabricate models with clinically acceptable accuracy.